2016
DOI: 10.1021/acs.jpclett.6b02302
|View full text |Cite
|
Sign up to set email alerts
|

Charged Particle Imaging of the Deprotonated Octatrienoic Acid Anion: Evidence for a Photoinduced Cyclization Reaction

Abstract: . (2016) 'Charged particle imaging of the deprotonated octatrienoic acid anion : evidence for a photoinduced cyclization reaction.', The journal of physical chemistry letters., 7 (22). pp. 4635-4640. Further information on publisher's website:https://doi.org/10.1021/acs.jpclett.6b02302Publisher's copyright statement:This document is the Accepted Manuscript version of a Published Work that appeared in nal form in The journal of physical chemistry letters, copyright c American Chemical Society after peer revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…This mechanism was later confirmed by Musbat et al using isotope labeling MS-MS [44]. Similar cyclization mechanisms have been shown before for larger carotenoids [47], and later photoelectron spectroscopy was used to demonstrate fragmentation via Diels-Alder cyclization of a small anionic polyene, [C 7 H 9 −CO 2 ] − [48]. Coughlan et al have shown that in solution the RPSB degrades in a process which also involves a Diels-Alder cyclization and forms a cyclic retinal derivative of mass 238 amu.…”
Section: Fragmentation Via Cyclizationsupporting
confidence: 57%
See 1 more Smart Citation
“…This mechanism was later confirmed by Musbat et al using isotope labeling MS-MS [44]. Similar cyclization mechanisms have been shown before for larger carotenoids [47], and later photoelectron spectroscopy was used to demonstrate fragmentation via Diels-Alder cyclization of a small anionic polyene, [C 7 H 9 −CO 2 ] − [48]. Coughlan et al have shown that in solution the RPSB degrades in a process which also involves a Diels-Alder cyclization and forms a cyclic retinal derivative of mass 238 amu.…”
Section: Fragmentation Via Cyclizationsupporting
confidence: 57%
“…We expect that in the near future, advances in IMS resolution through techniques such as structures for losseless ion manipulation (SLIM) and trapped ion mobility spectrometry (TIMS) may improve our understanding of RPSB isomerization. A way forward may be to study simpler RPSB derivatives [31,48]. The RPSB studies exemplify the importance of using IMS as a structure selection stage in action-spectroscopy experiments, which we believe will become more and more common in the future.…”
Section: Discussionmentioning
confidence: 94%
“…Similar dynamics have been observed following photoexcitation in anions that then undergo ground state reactions. 54 The NO2 − PE spectrum can in fact explain much of the spectral broadening observed in Figure 1. In Figure 7, representative 1D PE spectra are shown along with simulated PE spectra for direct detachment from pDNB − and NO2 − .…”
Section: Discussionmentioning
confidence: 95%
“…resonances) and dissociation will compete with autodetachment. 17,[34][35][36][37] The relative decrease of the intensity of the I − feature compared to the direct detachment channels of PtI2 − can arise from a number of reasons in addition to the one noted above: the favourability of a one-photon process over two-photon process, the large apparent photodetachment crosssection of PtI2 − , and the absorption profile to the excited states of PtI2 − . At the low-energy spectral end, we did not succeed in acquiring a spectrum at hv = 3.1 eV, in part because our OPO has very weak output here and the cross section for detachment from iodide is low (near-This is the author's peer reviewed, accepted manuscript.…”
Section: Please Cite This Article Asmentioning
confidence: 99%